Governance, business environment and foreign direct investments - Omer, Baris; Pelizzo, Riccardo (Lambert Academic Publishing, 2015)
In this paper we investigate the relationship between the quality of governance, the business environment and foreign direct investments. Looking at 49 countries in Africa, we present evidence supporting the claim that the quality of governance does affect the stability of policies and the quality of the business environment. However, our data analysis also reveals that neither the quality of governance nor the quality of the business environment have any impact, at least in Sub-Saharan Africa on the level of FDI.
Keywords: quality of governance; the business environment; governance